KONTRIBUSI KOMUNIKASI INTERPERSONAL DALAM PERSPEKTIF ISLAM DI LINGKUNGAN ORGANISASI UIN RADEN INTAN LAMPUNG - Muhammad Bisri Mustofa; Siti Wuryan; Nadya Amalia Sholiha; Malik Maulana Arif; Musa Musa (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
In today's modern era communication really needs to be used, because as the times progress the better communication needs to be applied. Interpersonal communication needs to be used in organizations, interpersonal communication is divided into 2 types, namely formal and non-formal communication. Formal communication is used at official events or during teaching and learning activities on campus. Non-formal communication is usually used when we communicate with peers. According to Adler and Elmhorst, (1996) explaining communication can also be interpreted as one of the most important skills that greatly influences a person's performance. And the method used in this research is by collecting respondents to find out how they communicate with their environment, so this research is aimed at finding out whether in the modern era like today people are able to communicate well in the community and in the organizational environment. The purpose of this research is to find out how well people understand how to communicate well.